Іgnition of the beam-plasma discharge in the initially neitral gas - Dadyka, D.I.; Anisimov, I.O. (Вопросы атомной науки и техники, 2018)
Initial stage of the beam-plasma discharge was studied via computer simulation for 2D electrostatic model. Stripped non-relativistic electron beam was injected into initially non-ionized helium. At the first stage transversal expansion of the beam was observed caused by its space charge. At the same time helium ionization via electron impact took place. Later beam focusing has been developed due to the space charge of the ions. Development of the beam-plasma instability as well as the background plasma heating was observed at the last stage of the simulation.